Reforming police human capital management through functional positions and competency-based appraisal systems: A systematic review (2020-2025) - Panuntun, Bagus; Runturambi, Arthur Josias Simon (Edelweiss Applied Science and Technology, 2025)
Strengthening the competence and professionalism of police officers is a strategic issue in security sector institutional reform in the era of disruption. This study aims to identify, synthesize, and systematically analyze scientific literature published between 2020 and 2025 that discusses functional position models and competency-based performance appraisal systems within the context of the National Police. A systematic literature review (SLR) approach was employed, guided by the PRISMA protocol, resulting in 87 articles selected from five internationally reputable databases. Thematic analysis grouped the findings into four main areas: competency enhancement, appraisal systems, restructuring of functional positions, and institutional integration. The results indicate a predominance of qualitative and mixed-methods approaches, with significant attention given to psychosocial well-being, equity in evaluation, and transformative leadership. The absence of an integrative model that systematically combines these three aspects reveals a conceptual gap in the literature. This study contributes a synthesized framework that integrates the technocratic and humanistic dimensions of police HRM and recommends an evidence-based, interdisciplinary research agenda.